COMPREHENSIVE ANALYSIS OF FACTORS INFLUENCING THE ATTRACTIVENESS OF THE INVESTMENT CLIMATE - Rakhmanov Sharof Diyorovich (American Journals, 2025)
The article reveals the relevance and importance of investment risk assessment and management mechanisms in the digital economy, conducts a comprehensive analysis of factors affecting the attractiveness of the investment environment, analyzes the attractiveness of the investment environment: the experiences of developed countries, and provides conclusions and proposals for increasing the attractiveness of the investment environment in our country.
Keywords: Investment climate, investment attractiveness, investment risks, financial stability, institutional factors, political stability, economic freedom, level of corruption, inflation rate, interest rates, infrastructure development.